Art, education and registration: the various forms of memory (Palíndromo, 2023)
The article starts from the issue of how to document what art teaching professionals plan in/for exhibitions in museums and cultural centers, presenting theoretical reflections that correlate the concepts of memory, archive and document. The text aims to discuss the relationship between document and memory in the cultural environment of Latin America, to point out how such links lead to different forms of registration and to provide reflection on the different ways that the memory of our educational practices in art can gain, as we integrate with our cultural landscape. The writing presents results of a bibliographical and field research (this one carried out in Lima, Peru), referenced in readings of the fields of art, education, history and semiotics of culture, from authors such as Artières (1998), Farge (2009), Lotman (1998), Pinheiro (2020), Sennet (2020), Taylor (2013) and Zumthor (1993). Among the results, we emphasize the understanding that choosing the most appropriate way to record a memory is related to what is considered to be remembered and that including these other forms of manifestation of memory expands what we understand by knowledge.
Keywords: Museum education; Archives in education; Art teaching